Pengaruh Inovasi Produk dan Kualitas Produk terhadap Keputusan Pembelian Jersey Custom di Republic Jersey Bekasi - Ananda Ihtiar Al Islami; Anita Maulina; Anisa Arizona Bandi (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aimed to determine how much influence product innovation andproduct quality had on the purchasing decisions of customized jerseys in Republic Jersey Bekasi. This study employed a quantitative approach by using a survey method. The sample in this study were customers who had ordered customized jerseys at Republic Jersey at least once and obtained as many as 160 respondents. The data were analyzed using multiple linear regression. The results of this study indicated that Product Innovation (X1) partially positively and significantly affected Purchasing Decisions (Y) for customized jerseys in Republic Jersey Bekasi by 29.5%. Product Quality (X2) positively and significantly affected Purchasing Decisions (Y) for customized jerseys in Republic Jersey Bekasi by 46.3%. Taken together, Product Innovation (X1)and Product Quality (X2) had a positive and significant effect on PurchasingDecision (Y) customized jerseys in Republic Jersey Bekasi by 48.5%. Last, the remaining 51.5% was influenced by other variables that were notresearched such as promotion, prices and location